Terrorism and General Aviation - Bryan LaBrecque; Rodger A. Bates (Journal of Public and Professional Sociology)
Terrorism is an increasingly significant threat to society. It has evolved as technology has become a significant force multiplier in terms of its impact on society. Almost since the dawn of aviation, the potential threat to and from aviation has increased as it has become an intrinsic element within the transportation system of our nation. Since the middle of the 20th century, commercial aviation has been the primary arena of transportation terrorism. However, with the increased attention and development of effective counterterrorism capabilities, terrorists are seeking alternative targets. America’s General Aviation community is a system at risk. From a tactical perspective, General Aviation provides relatively easy access to planes as a tool for terrorism. Likewise, the threat of terrorism also may be a significant economic and symbolic weapon that may ultimately impact the field of transportation security within the United States.